Prediction of the sphenopalatine ganglion localization in computerized tomography images. (7th February 2019) - Crespi, Joan; Bratbak, Daniel; Dodick, David; Matharu, Manjit; Jamtøy, Kent Are; Tronvik, Erling
Background: The sphenopalatine ganglion (SPG) is a target for several headache syndromes. Most of the groups targeting the SPG do not localize it directly, and this might account for some therapeutic failures. As the SPG cannot be seen on computerized tomography (CT) scans, magnetic resonance image (MRI) must be used to visualize the ganglion. It would be advantageous to be able to predict the location of the SPG on CT scans for those using fluoroscopy or CT-guided injections and for those in whom MRI is not accessible or contraindicated. Methods: We localized the SPG in 21 Caucasian patients (21 right and 17 left ganglia; total 38) in 3 tesla MR images subsequently fused with CT scans. We measured the distance from the SPG to two bony landmarks identified on CT scans. We then applied the average distances to find an estimated position of the SPG. The first landmark was the center of the anterior opening of the vidian canal (VC). The second landmark was a point on the sphenoidal bone, defined in an axial plane at the level of the center of the VC (S-point). The predicted position of the SPG measured from the VC and the sphenoidal bone were referred to as, respectively, vcSPG and sSPG. Finally, the distances between the SPG, as seen on MRI, and predicted vcSPG/sSPG were calculated. Results: The average distance between SPG as seen on the MRI images and the estimated position based on CT images were 1.82 mm (SD 0.83, range 0.22–3.57 mm) for vcSPG and 2.09 mm (SD 0.99, range 0.71–4.79 mm) for sSPG. Conclusions: The localization of the SPG can be predicted on CT images using bony landmarks. Localization of the SPG may be important in achieving successful therapeutic outcomes for treatments that are directed toward the SPG.